Adventures on the Routes of Protein Evolution—In Memoriam Dan Salah Tawfik (1955–2021). Issue 7 (15th April 2022) - Jackson, Colin; Toth-Petroczy, Agnes; Kolodny, Rachel; Hollfelder, Florian; Fuxreiter, Monika; Kamerlin, Shina Caroline Lynn; Tokuriki, Nobuhiko
Graphical abstract: Highlights: De novo enzyme design. Basis of catalytic promiscuity. High-throughput screening of enzyme libraries. Function-stability tradeoffs. Origin of life. Abstract: Understanding how proteins evolved not only resolves mysteries of the past, but also helps address challenges of the future, particularly those relating to the design and engineering of new protein functions. Here we review the work of Dan S. Tawfik, one of the pioneers of this area, highlighting his seminal contributions in diverse fields such as protein design, high throughput screening, protein stability, fundamental enzyme-catalyzed reactions and promiscuity, that underpin biology and the origins of life. We discuss the influence of his work on how our models of enzyme and protein function have developed and how the main driving forces of molecular evolution were elucidated. The discovery of the rugged routes of evolution has enabled many practical applications, some which are now widely used.